MERANCANG LEMBAR AKTIVITAS DAN PORTOFOLIO KERJA SISWA TINGKAT SEKOLAH DASAR : (Sebagai Upaya Mencapai Tujuan Pembelajaran yang Efektif) - Choirul Anam Balqis (Abtadi : Jurnal Pendidikan Dasar, 2022)
ABSTRACT Based on what happened in several schools, the fact is that teachers lack creativity to plan, prepare and make teaching materials that are rich in innovation so that they are attractive to students. This is of course a problem in learning at school. From these problems the author formulated the purpose of this paper, namely to describe the definition of activity sheets and student work portfolios, explain the techniques of activition sheets and student work portfolios and how to design activity sheets and student working portfolios. Research of the type used is library research with a descriptive qualitative approach. Library research is a seri of study relation to various data or various materials originating from libraries in the form of books, encyclopedias, dictionaries, journals, documents, magazines and so on. Student activity sheets are worksheets that students must work on which contain instructions for completing assignments so that students can find structured directions to understand the material being studied. While student work portfolios are all collections of work results in a subject or competency in a certain period of time. an assignment, reflection or student self-assessment results, and student journals or diaries. The technique in designing student activity sheets is to review and explore the material students will study starting from basic competencies, indicators, learning outcomes and scientific systematics; identify the type of process skills that will be developed when studying the material; determine the form of LAS in accordance with the material to be taughting; designing activities to be displayed on student activity sheets in accordance with the process skills developed; organize designs into LAS with an attractive layout, easy to read and use; test LAS whether it can be used by students and see the shortcomings and revise LAS. While student work portfolios can consist of: 1) introduction, 2) table of contents, 3) results of self-assessment or reflection, and 4) student journals or diaries or periodical notes on a topic. A quality student activity sheet (LAS) must meet and follow LAS procedures. The steps are: 1) Defining stage, 2) Student analysis stage, 3) Compilation stage, 4) Task analysis stage, 5) Format selection stage 6), Limited trial stage, 7) Field trial stage. Several stages for designing and making student activity sheets must be observed so that they are in accordance with the learning objective to be achieved. Likewise with making portfolios, things that need to be considered by teachers when designing student work portfolios, namely objectives, content, management, and assessment. The teacher needs to prepare a special book to make various portfolio notes